Recent decline in body condition of departing Common Guillemots Uria aalge at Hornøya, North Norway - Barrett, Robert T. (Norsk Ornitologisk Forening, 2010)
Since 1980, there has been large variation and a recent decline in the mass and body condition of Common Guillemot Uria aalge chicks departing from the nest site in NE Norway. This may be related to deterioration in the feeding conditions off the colony and is alarming considering the critically endangered status of the species in Norway. To measure body condition, earlier studies have caught, weighed and measured guillemot chicks either while still on the breeding site or as they leave the colony. This study emphasises the importance of choosing and defining which method to use as they give different results.